Glass, in particular as cover plate

By optimizing the glass composition and heat treatment technology, the problem of difficulty in processing existing glass is solved, and a chemically tempered glass with high mechanical strength, low cost and good manufacturing ease is prepared, which is suitable for the manufacture of glass covers.

CN119569333APending Publication Date: 2025-03-07SCHOTT AG +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411235041.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-09-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, difficult-to-process glasses are difficult to meet the needs of glass covers, especially with challenges in terms of mechanical strength, cost and ease of manufacturing.

Method used

By optimizing the composition of the glass, including the ratios of SiO2, Al2O3, Li2O, B2O3, Na2O and K2O, combined with appropriate heat treatment and ion exchange techniques, a chemically tempered glass that is easy to melt, clarify and thermoform is prepared.

Benefits of technology

The low-cost manufacturing of glass is achieved, which improves its mechanical strength and chemical resistance, while reducing the thermal expansion coefficient of glass, ensuring stress-free cooling after thermal forming, and improving the overall performance of the glass cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027497230000121
    Figure BDA0005027497230000121
  • Figure BDA0005027497230000131
    Figure BDA0005027497230000131
  • Figure BDA0005027497230000141
    Figure BDA0005027497230000141
Patent Text Reader

Abstract

The present disclosure describes an LABS glass that can be chemically tempered or that is chemically tempered. A method for manufacturing the glass, a cover sheet made of such a glass and its use and a digital display device comprising such a cover sheet are also described.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a chemically toughened or chemically toughened glass, a method for manufacturing the glass, a cover plate made of the glass and its use, and a digital display device comprising the cover plate. Background Art

[0002] It is already known to use glass or glass ceramics as cover plates for electronic components and displays, in particular for smartphones. These glass-based materials are preferably chemically toughened in order to increase their mechanical strength.

[0003] Glasses of the Li2O-Al2O3-SiO2 system, so-called LAS glasses, have proven to be particularly suitable. These glasses have SiO2, Li2O and Al2O3 as their main components. One subgroup of LAS glasses is boron-containing LAS glasses, also called LABS glasses.

[0004] Compared to AS glass (i.e., glass without lithium), LAS glass has the advantage, in particular with regard to use as a covering material, that it can be chemically toughened very well by ion exchange of lithium ions with sodium ions or by combined ion exchange of lithium ions with sodium ions and sodium ions with potassium ions, and thus has a higher mechanical strength against so-called "sharp impact loads" (i.e., against impacts of rough surfaces and sharp objects) and against impacts of blunt or smooth surfaces (i.e., against so-called "blunt impact loads"). In this case, LABS glass is preferred to LAS glass, since the addition of B2O3 strengthens the connection of the glass network and further improves mechanical properties, such as scratch resistance.

[0005] Such glasses have been disclosed in the prior art.

[0006] US 2017 / 197869 A describes LABS glasses which, according to the example, have a relatively high expansion coefficient and a low Li2O fraction relative to the total alkali metal oxide content.

[0007] US 2018 / 186685 A also describes LABS and LAS glasses. LABS glasses have a low Li2O content, in particular relative to the total alkali metal oxide content.

[0008] US 2018 / 127302 A describes LABS glasses having a relatively low Li2O content relative to the total alkali metal oxide content and / or having a relatively high boron content.

[0009] US2020 / 317558 A describes AS glasses, ie lithium-free glasses or LA(B)S glasses, which have a relatively low lithium content and / or do not contain B2O3.

[0010] DE 10 2019 121 146 A describes LAS glass with the lowest content of nucleating agents ZrO2, SnO2 and TiO2.

[0011] DE 10 2019 121 143 A describes LAS glass with a relatively high content of alkali metal oxides, especially Na2O.

[0012] The common feature of the prior art glasses with the above-mentioned good product properties is that they are difficult to process. This is related to both the behavior of the glass melt in the clarification region and the behavior of the glass during forming and cooling, and also related to the easy crystallinity of the glass. Summary of the Invention

[0013] Therefore, the object of the present invention is to provide a chemically temperable or tempered glass, especially for use as a glass cover, which is easy to melt, clarify and thermoform based on its viscosity properties and can be manufactured at a relatively low cost. Of course, the glass should also have the product properties required for its intended use in the tempered state.

[0014] Other aspects of the present invention relate to a method for manufacturing such glass, a cover plate made of such glass and its uses, and a digital display device comprising such a cover plate.

[0015] The solution of the present invention to achieve the above object lies in the subject matter of the independent claims. Specific and preferred technical solutions can be found in the dependent claims and the description of the present disclosure.

[0016] The chemically temperable or chemically tempered glass according to the present invention comprises SiO2, Al2O3, Li2O and B2O3 and optionally Na2O and optionally K2O as components.

[0017] In this case, for the B2O3 content (in mol%, based on oxides), 0.1 < B2O3 ≤ 8.5 is applicable; preferably 0.1 < B2O3 < 8.5.

[0018] The above-mentioned minimum B2O3 content is necessary for a low devitrification upper limit. The devitrification upper limit is the temperature at which the glass is heated from room temperature and held for one hour without crystals. Generally, LABS glass crystallizes when heated in a temperature range above the glass transition temperature Tg. If the temperature is further increased, the crystals will dissolve again. Based on the viscosity of the glass, it may dissolve slowly, so this temperature needs to be held for 1 hour. The devitrification upper limit is a measure of the easy crystallinity of the glass. If this devitrification upper limit is low, it advantageously indicates that the glass is not easy to crystallize (the crystals are quite "unstable" and will dissolve even at low temperatures), so it is easier to produce.

[0019] Above the above B2O3 content, segregation may occur and it is not conducive to ionic diffusion, especially the diffusion of potassium ions.

[0020] For alkali metal oxides Li2O, Na2O, and K2O (all contents are in mol%), the following applies:

[0021] 0.8 < Li2O / (Li2O + K2O + Na2O) ≤ 1.

[0022] In this case, this condition can be met by containing all three of the above alkali metal oxides or by containing Li2O together with K2O or together with Na2O or by containing only Li2O (Li2O / (Li2O + K2O + Na2O) = 1).

[0023] It is preferred to use a ratio of Li2O / (Li2O + K2O + Na2O) < 1.

[0024] The devitrification upper limit temperature OEG of the chemically temperable or chemically tempered glass according to the invention is 10 K or less higher than the processing temperature VA, preferably lower than the processing temperature. This can avoid the uncontrolled crystallization of undesired crystal phases during the manufacturing process, especially during thermoforming. These undesired crystal phases can be, for example, spodumene, hydrothermal quartz, forsterite, baddeleyite, zinc spinel.

[0025] In this case, the processing temperature VA, i.e., the temperature at a viscosity of 10 4 dPas, is preferably lower than 1300 °C, preferably lower than 1260 °C, particularly preferably lower than 1220 °C. This is beneficial for forming, especially for setting a small and uniform glass thickness, especially in a float bath.

[0026] The temperature of the glass at a viscosity of 10 2 dPas (referred to as T2) does not exceed 1800 °C, preferably is lower than 1750 °C, particularly preferably is lower than 1720 °C. This makes the glass easy to clarify and has good optical quality as a product, without gas inclusions, i.e., without scattering.

[0027] The thermal expansion coefficient CTE20 - 300 of the glass is less than 5.4 ppm / K. This can achieve stress-free cooling after the thermoforming process. The thermal expansion coefficient CTE20 - 300 of the glass is preferably greater than 3.8 ppm / K.

[0028] The glass according to the invention having the above properties can be achieved by LABS glass, the composition of which has the said characteristics:

[0029] 0.1 < B2O3 ≤ 8.5 and 0.8 < Li2O / (Li2O + K2O + Na2O) ≤ 1.

[0030] The glass preferably has good chemical resistance in both the untempered and tempered state, i.e. class 3 or higher. Hydrolysis resistance H according to DIN 52296: Glass and glass ceramics: Water resistance of surfaces of glass and glass ceramic panels at 98°C, test method and classification (amendment: determination of other cations by ICP) (December 1989)

[0031] Alkali resistance L, according to DIN ISO 695: Glass: Resistance to attack by boiling mixed aqueous alkali solutions, test methods and classification (February 1994)

[0032] and acid resistance S according to DIN 12116: Test method and classification of the resistance of glass to attack by boiling aqueous hydrochloric acid solutions (March 2001).

[0033] Within the scope of the present disclosure, the composition of the glass is given in mol % based on the oxides.

[0034] In a preferred embodiment, the amounts of these components are (based on oxides, in mol%): SiO2 62-72, preferably 65-70

[0035] and / or

[0036] Al2O3 7-14, preferably 8-12

[0037] and / or

[0038] B2O3 0.1-8.5, preferably <8.5 or ≤8, preferably 4-7, particularly preferably ≥5, particularly preferably >5.5 and / or

[0039] Li2O 5-12, preferably 7-10

[0040] and / or

[0041] Na2O 0-2, preferably 0-1, particularly preferably ≥0.1 and / or <1, ​​particularly preferably ≥0.3 and / or <0.8

[0042] and / or

[0043] K2O 0-2, preferably 0-1.

[0044] The presence of SiO2, preferably with a minimum content of 62 mol% or even 65 mol%, is necessary for the formation of a stable glass network, which increases the mechanical stability and chemical resistance of the glass. SiO2 increases the viscosity of the melt. Excessively high contents should be avoided in order to achieve solubility and to obtain a sufficiently low viscosity during fining to allow the bubbles to rise. Therefore, the maximum content of SiO2 is preferably limited to 72 mol%, particularly preferably to 70 mol%.

[0045] It is necessary to contain Al2O3, preferably with a minimum content of 7 mol% or even 8 mol%, in order to achieve rapid alkali diffusion in the glass and to generate higher compressive stresses (CS30 and CS50 values). If the Al2O3 content is too high, the crystallization tendency of the glass will increase significantly. Therefore, the maximum content of Al2O3 is preferably limited to 14 mol%, particularly preferably to 12 mol%.

[0046] The presence of B2O3 and preferably a minimum content of 4 mol% or 5 mol% or more or even 5.5 mol% or more has a positive effect on the meltability. If the content exceeds the preferred upper limit of 8.5 mol%, a slight decrease in chemical resistance, CS30 and CS50 values ​​will result. Therefore, the B2O3 content is preferably limited to less than 8.5 mol% or not more than 8 mol%, particularly preferably not more than 7 mol%.

[0047] The presence of Li2O, preferably with a minimum content of 5 mol %, particularly preferably with a minimum content of 7 mol %, enables chemical tempering of the glass in a sodium salt bath. The Li2O content is preferably limited to 12 mol %, particularly preferably to 10 mol %, otherwise the crystallization tendency increases sharply, in particular in the case of precipitation of Li2O (and Al2O3)-containing crystalline phases such as spodumene or keatnetite.

[0048] If Na2O is contained, its content is particularly preferably at least 0.1 mol%, particularly preferably at least 0.3 mol%, which is beneficial to achieve solubility and inhibit crystallization. Based on the negative influence on compressive stress (CS30 and CS50 values) and the increase in the thermal expansion coefficient, its maximum content is preferably limited to 2 mol%, particularly preferably to 1 mol%, and particularly preferably to less than 1 mol%.

[0049] If K2O is present, it has a positive effect on the meltability. In addition, K2O in the glass increases K diffusion and enables deeper tempering (K-DoL) in the last tempering step during multi-stage tempering. The K2O content is preferably limited to 1 mol%, since too high a K2O content has a negative effect on K-induced tempering (KCS).

[0050] In a further preferred embodiment, the glass may include the following components (based on oxides, in mol %):

[0051] MgO 0-5, preferably 0.5-3

[0052] and / or

[0053] CaO 0-8, preferably 1-6

[0054] and / or

[0055] SrO 0-5, preferably 0-1

[0056] and / or

[0057] BaO 0-2

[0058] and / or

[0059] ZnO 0-5, preferably 0-1

[0060] and / or

[0061] P2O5 0-5, preferably 0.5-2

[0062] and / or

[0063] ZrO2 0-5, preferably 0-3.

[0064] In order to reduce the viscosity of the glass and thereby increase the manufacturability, alkaline earth metal oxides and / or ZnO can be used.

[0065] If ZnO is present, its content is preferably limited to less than 5 mol %, particularly preferably to less than 1 mol %, since higher contents may cause evaporation during the melting process and corrosion of refractory materials in glass production.

[0066] If MgO is present, it preferably has a minimum content of 0.5 mol%, which has a positive effect on solubility. Contents above 5 mol% are beneficial to crystallization and are therefore preferably avoided. Therefore, in some embodiments, this content is also limited to a maximum of 3 mol%.

[0067] If CaO is contained, preferably in a minimum content of 1 mol%, it helps to achieve the desired lower upper devitrification temperature OEG.

[0068] If SrO is present, its content is preferably limited to less than 5 mol %, particularly preferably less than 1 mol %, because at higher contents, alkali diffusion in the glass during chemical tempering is reduced and very long tempering times may be required or only lower DoCL values ​​can be achieved.

[0069] If BaO is present, its content is preferably limited to less than 2 mol%. The glass is preferably substantially free of BaO.

[0070] If P2O5 is contained, preferably with a minimum content of 0.5 mol%, the diffusion of alkali in the glass will be positively influenced. This has the advantage that the time of ion exchange can be shortened. The P2O5 content should preferably not exceed 5 mol%, particularly preferably not exceed 2 mol%, because too high a content may cause corrosion of refractory materials in glassmaking.

[0071] If ZrO2 is contained, it has a positive effect on the chemical resistance of the glass. However, a higher ZrO2 content promotes devitrification. Therefore, its maximum content is preferably limited to 5 mol%, particularly preferably limited to 3 mol%, very particularly preferably limited to 2 mol% or even limited to only 1 mol%.

[0072] The glass may also contain TiO2, for example. If TiO2 is contained, its content is preferably limited to less than 2 mol%. The glass preferably contains substantially no TiO2.

[0073] "Substantially no" means that only impurities that cannot be avoided in the case of conventional economic treatment methods are contained (for example, impurities that cannot be avoided due to raw materials).

[0074] It has been confirmed that a specific relationship between these components is very advantageous for the glass and its manufacturability and chemical temperability. Therefore, the composition of the glass is preferably selected in a specific manner such that for these components (based on oxides, in mol%), the following applies:

[0075] 0.9 < (Al2O3 + B2O3 + ZrO2) / (R2O + RO) < 1.7;

[0076] Preferably 1 < (Al2O3 + B2O3 + ZrO2) / (R2O + RO) < 1.6;

[0077] Particularly preferably 1.1 < (Al2O3 + B2O3 + ZrO2) / (R2O + RO) < 1.5

[0078] and / or

[0079] 0.5 < Al2O3 / (R2O + RO) < 1.1;

[0080] Preferably 0.6 < Al2O3 / (R2O + RO) < 0.9;

[0081] Particularly preferably 0.7 < Al2O3 / (R2O + RO) < 0.85

[0082] where R2O = Li2O + K2O + Na2O, and

[0083] RO = MgO + CaO + SrO + BaO + ZnO.

[0084] In this case, a ratio of 0.5 < Al2O3 / (R2O + RO) < 1.1 is favorable for glass formation.

[0085] If the ratio of Al2O3 / (R2O+RO) is greater than 1.1, the tendency of the crystals to form Al2O3-containing crystals increases dramatically, since there is no longer enough R2O and RO to "dissolve" all of the Al2O3 in the glass. If the ratio of Al2O3 / (R2O+RO) is less than 0.5, there are too many non-bonded bridging oxygens and alkali diffusion is reduced, since the negative charge is concentrated on a single oxygen anion and no longer dispersed throughout the AlO4 tetrahedron. This increases the electrostatic bonding of mobile alkali cations to the glass matrix and impairs chemical toughening.

[0086] The ratio of 0.9 < (Al2O3 + B2O3 + ZrO2) / (R2O + RO) < 1.7 has a positive effect on the connectivity and mechanical stability of the glass network. This ratio also ensures that the boron cations are preferably present in tricoordinated form with oxygen and not as tetrahedral BO4 units. The tetrahedral BO4 units have a strong negative influence on the diffusion of alkalis, in particular potassium cations.

[0087] In an embodiment, the glass may contain 0 to 1 mol % SnO2, preferably 0.1 to 0.5 mol % SnO2 and / or 0 to 1 mol % CeO2 and / or 0 to 1 mol % Cl, wherein the sum of CeO2+SnO2+Cl is preferably at most 2 mol %.

[0088] In an embodiment, the glass may contain no more than 2 mol %, preferably no more than 1 mol %, of conventional refining agents such as As2O3, Sb2O3, SnO2, CeO2, halides (preferably chlorides) or sulfur-containing compounds. For reasons of environmental protection and work safety, in particular when the glass is manufactured using the float process, the glass is preferably substantially free of arsenic and antimony. This also applies to other toxic or environmentally harmful components such as PbO, TeO2, CdO.

[0089] In addition, in particular when used as a front cover (i.e. as a so-called front cover), the glass is preferably essentially free of coloring components, in particular free of coloring rare earths, in particular Nd2O3, Er2O3 and coloring metal oxides, in particular V2O5, CoO, NiO, Cr2O3, CuO.

[0090] At a thickness of 0.6 mm, the average transmission of such a colorless glass in the range of 365 to 640 nm is preferably at least 85%.

[0091] In particular, when the glass is used as a back cover (i.e. as a so-called back cover), it preferably contains a coloring component, for example at least 0.1 mol % and at most 5 mol % of at least one coloring component, particularly preferably selected from CoO, Fe2O3, TiO2, Cr2O3 and / or MnO and / or mixtures thereof.

[0092] The iron content in the glass (given as a percentage by weight of Fe2O3) should preferably be less than 1000 ppm, particularly preferably less than 500 ppm, in order to avoid undesired coloring of the material. In this case, the iron content in the glass results from unavoidable impurities in the raw materials. By using raw materials with a low iron content, the iron content can be reduced and a better (more neutral) natural color of the glass can be obtained, although this is generally associated with higher raw material costs.

[0093] The glass according to the invention is generally suitable for producing cover plates, for example for electronic devices, in particular electronic display devices, in particular mobile electronic display devices, for example mobile touch panels and / or mobile digital display devices, such as smartphones or smart watches and touch panels.

[0094] The thickness of the cover plate is preferably 0.3 mm to 1 mm, preferably 0.35 mm to 0.7 mm, particularly preferably 0.4 mm to 0.65 mm.

[0095] The method for manufacturing glass comprises the following steps:

[0096] - manufacturing silicate glass by a fusion process, and

[0097] - fining of glass melts, and

[0098] - Subsequent thermoforming.

[0099] Without limiting the generality, the thermoforming may be performed, for example, by a stretching process, in particular a float process, or a down-draw process, such as an overflow fusion or a stretch nozzle process.

[0100] In order to manufacture the tempered glass used as a cover plate according to one embodiment, the following steps are performed after the above steps:

[0101] - Carry out at least one ion exchange in an exchange bath whose composition is 100wt% to 0wt% KNO3 and 0wt% to 100wt% NaNO3 and 0wt% to 5wt% LiNO3, the temperature of the exchange bath is between 370°C and 500°C, and the duration is 1 hour to 50 hours.

[0102] It is also possible to carry out ion exchange in more than one exchange bath, for example firstly in an exchange bath having a composition of 50 wt % to 0 wt % KNO3 and 50 wt % to 100 wt % NaNO3 and 0 wt % to 5 wt % LiNO3, the temperature of the exchange bath being between 370° C. and 500° C. and the duration being between 1 hour and 20 hours,

[0103] A further ion exchange is then carried out in an exchange bath having a composition of 100 wt % to 50 wt % KNO 3 , 0 wt % to 50 wt % NaNO 3 and 0 wt % to 5 wt % LiNO 3 , the temperature of the exchange bath being between 370° C. and 500° C. and the duration being between 1 hour and 20 hours.

[0104] Furthermore, ion exchange may also be performed in three or more exchange baths.

[0105] The cover plate made of tempered glass has higher strength.

[0106] The proportion of Li2O in the total alkali content of LABS glass is relatively high, that is, expressed as Li2O / (Li2O+K2O+Na2O)>0.8. Therefore, even if the glass thickness is small, good tempering values ​​can be achieved during the tempering process, that is, higher tempering values ​​CS (that is, CS30>100MPa) are achieved on the surface and near the surface and higher tempering values ​​CS (that is, CS50>80MPa) are achieved near the depth of the compressive stress zone, and a deeper compressive stress zone DoCL is achieved, that is, DoCL>0.17*t, where t is the thickness of the glass sheet.

[0107] In this case,

[0108] CS30, in MPa, refers to the compressive stress at 30 μm from the main surface.

[0109] CS50, in MPa, refers to the compressive stress at 50 μm from the surface of the same main surface. DoCL, in μm like the thickness of the glass plate, refers to the depth of the compressive stress zone on the same main surface.

[0110] The main surface is the surface of the glass plate with the largest area relative to the other surfaces. In addition to the two main surfaces, the glass plate preferably also has four surfaces connected to the two main surfaces, which are called sides. In the case of non-rectangular glass plates, the glass plate can also have fewer sides, for example only one side.

[0111] This tempering process is chemical tempering and is preferably carried out by immersing the glass sheet in an exchange bath, but can also be carried out by applying a slurry to the glass sheet.

[0112] An exchange bath refers to a molten salt, wherein the molten salt is used in an ion exchange process for glass or glass products. Within the scope of the present disclosure, the terms exchange bath and ion exchange bath are used synonymously.

[0113] Technically pure salts are usually used for the exchange bath. This means that, although, for example, only sodium nitrate is used as starting material for the exchange bath, the exchange bath may still contain certain impurities. In this case, the exchange bath is a melt of a salt, for example sodium nitrate, or a mixture of salts, for example a mixture of sodium and potassium salts. In this case, the composition of the exchange bath is given in a form such that it relates to the nominal composition of the exchange bath, without taking into account any impurities that may be present. Therefore, within the scope of the present disclosure, if a 100% sodium nitrate melt is mentioned, this means that only sodium nitrate is used as raw material. However, the actual content of sodium nitrate in the exchange bath may deviate from this and usually does so, since technical raw materials, in particular, have a certain amount of impurities. However, this impurity amount is usually less than 5% by weight, in particular less than 1% by weight, relative to the total weight of the exchange bath.

[0114] For exchange baths with mixtures of different salts, the nominal contents of these salts are given accordingly, without taking into account any technically relevant impurities in the starting materials. Thus, an exchange bath with 90 wt. % KNO3 and 10 wt. % NaNO3 can still have small amounts of impurities, but these are caused by the starting materials and their content should generally be below 5 wt. %, in particular below 1 wt. %, relative to the total weight of the exchange bath.

[0115] Furthermore, during the ion exchange process, the composition of the exchange bath may also change, since lithium ions migrate from the glass or glass product into the exchange bath as a result of the ongoing ion exchange. However, unless expressly stated otherwise, such changes in the composition of the exchange bath due to aging are also not taken into account here. Rather, within the scope of the present disclosure, the specification of the composition of the exchange bath is based on the nominal original composition. DETAILED DESCRIPTION

[0116] The present invention is described in detail below with reference to examples.

[0117] Table 1 lists the composition of examples of glasses according to the invention (all data are in mole percent based on oxides). Table 2 lists the composition of comparative glasses (names beginning with V) (all data are in mole percent based on oxides).

[0118] The materials listed in Tables 1 and 2 were melted and refined at a temperature of 1550° C. to 1680° C. using raw materials commonly used in the glass industry. In this case, the mixture was first melted in a Pt / Rh crucible at 1550° C. to 1650° C. This melt was then refined at a temperature of 1650° C. to 1680° C. and subsequently homogenized by stirring for 30 minutes. After standing for 2 hours at 1550° C. to 1650° C., castings with a size of about 140 mm x 100 mm x 30 mm were cast and these castings were stress relieved in an annealing furnace at about 500° C. to 650° C. and cooled to room temperature. Test specimens for measuring the properties in the untempered state were prepared from these castings. The thickness of the samples for the tempering tests was about 0.5 mm.

[0119] Tables 1 and 2 give the following properties for the glasses according to the invention and the comparative glasses:

[0120] Thermal expansion coefficient CTE20-300, measured by dilatation method, unit: ppm / K;

[0121] Transition temperature Tg, measured by dilatography, in °C;

[0122] Viscosity: 10 2 The temperature at dPas, called T2, is in °C and is calculated by the Vogel-Fulcher-Tammann (VFT) equation;

[0123] The VFT curve describes the common logarithm of the viscosity as a function of the temperature T with the aid of the three parameters A, B and T0:

[0124] lg(|η|)=A+B / (T-T0);

[0125] The VFT parameters (A, B, T0) are determined by fitting the measured data of viscosity and temperature with the help of a VFT function;

[0126] Density ρ, in g / cm 3 ;

[0127] Viscosity: 10 4 The temperature at which dPas is called the processing temperature VA, in °C, is measured with the aid of a stirring viscometer;

[0128] Viscosity: 10 3 The temperature at which dPas is called T3, in °C, is measured with the aid of a stirring viscometer;

[0129] The devitrification upper limit temperature, called OEG, is measured in °C by temperature gradient. In this case, glass sand is placed on a platinum support in a gradient furnace and temperature-controlled for one hour. The platinum support is then removed together with the glass. The temperature at the hot end of the gradient, where the glass contains no crystals, is called the devitrification upper limit temperature. In this case, the crystals in the glass sample are examined with the aid of an optical microscope.

[0130] The common logarithm of the liquidus viscosity, called lg (liquidus viscosity), is measured in dPa*s, at the upper temperature limit of devitrification, according to lg(|η|)=A+B / (OEG-T0) based on the VFT parameters A, B, T0 and OEG.

[0131] The abbreviation "nb" in the tables means "not determined".

[0132] Specific Examples

[0133]

[0134]

[0135]

[0136]

[0137] Comparative Example V1 has an excessively high coefficient of thermal expansion, and therefore generates relatively large stresses during cooling, which, especially in the case of thin glass, may cause the glass to bend and / or crack.

[0138] Comparative Example V15 has too high a T2 temperature, so that the melt is too viscous at the temperature used in industrial glass production, and bubbles can only be incompletely removed in the fining step, resulting in a low yield.

[0139] Comparative Examples V2 to V14 have unfavorable positions of OEG and VA relative to each other. As a result, the viscosity range in which crystals can be formed starts earlier from the hot melt, and the devitrification region increases overall. This is not conducive to producing such glasses with good yields.

[0140] The OEG, VA, T2 and CTE data of the examples show that the glasses according to the invention can be processed very well.

[0141] In particular, in the case of relatively small thicknesses (e.g. in the range of 0.3 mm to 0.7 mm), the glass can be produced with good yields. Such a glass is less susceptible to crystallization. The stresses in the cooling zone, which are likely to occur in particular in the float process due to the different cooling methods of the thin glass web and the thick glass edge, can be avoided to a large extent.

[0142] The glass according to the present invention can be easily chemically toughened.

[0143] If a sample having the components of the example is subjected to ion exchange under the following conditions:

[0144] - ion exchange in a bath of 20 wt% KNO3 and 80 wt% NaNO3 at 420°C for 7.5 hours, and

[0145] - further ion exchange in an exchange bath consisting of 100 wt% KNO3 and 0 wt% NaNO3 at a temperature of 390°C for a duration of 3 hours,

[0146] As shown in the following table for example glasses 6, 7, 8 and 9, which gives the values ​​of CT (=central tension, i.e. tensile stress), CS30, CS50 and DoCL as well as the values ​​of K-CS and K-DOL, these samples have the following properties:

[0147]

[0148]

[0149] Table 3

[0150] The chemically tempered glass according to the present invention has the following properties:

[0151] CT>80MPa, preferably CT>100MPa; CS30>100MPa, CS50>80MPa and DoCL>0.17*t.

[0152] The glass according to the invention is therefore very suitable in the tempered state for use as a cover plate for the above-mentioned applications; it combines good product properties with very good manufacturing and processing properties.

Claims

1. A chemically toughened or chemically toughened glass comprising SiO2, Al2O3, Li2O and B2O3 and optionally Na2O and optionally K2O, characterized in that With regard to the stated compositions (in mol %, based on the oxides), the following applies: 0.8 <Li2O / (Li2O+K2O+Na2O)≤1; 0.1 <B2O3≤8.5。 2. Preferably, the chemically toughened or chemically toughened glass according to claim 1, characterized in that: The devitrification upper limit temperature OEG is 10K or less higher than the processing temperature, preferably lower than the processing temperature VA, wherein the processing temperature VA is preferably lower than 1300°C, preferably lower than 1260°C, particularly preferably lower than 1220°C, and Viscosity: 10 2 dPas at temperatures up to 1800°C, and The coefficient of thermal expansion CTE20-300 is less than 5.4ppm / K.

3. The glass according to claim 1 or 2, characterized in that: The glass comprises the following components (based on oxides, in mol %): SiO2 62-72, preferably 65-70 Al2O3 7-14, preferably 8-12 B2O3 0.1-8.5, preferably <8.5 or ≤8, preferably 4-7, particularly preferably ≥5, particularly preferably >5.5 Li2O 5-12, preferably 7-10 Na2O 0-2, preferably 0-1, particularly preferably ≥0.1 and / or <1, ​​particularly preferably ≥0.3 and / or <0.8 K2O 0-2, preferably 0-1.

4. Glass according to any one of the preceding claims, characterized in that The glass comprises the following components (based on oxides, in mol %): MgO 0-5, preferably 0.5-3 CaO 0-8, preferably 1-6 SrO 0-5, preferably 0-1 BaO 0-2 ZnO 0-5, preferably 0-1 P2O5 0-5, preferably 0.5-2 ZrO2 0-5, preferably 0-3.

5. Glass according to any one of the preceding claims, characterized in that With regard to the stated compositions (in mol %, based on the oxides), the following applies: 0.9<(Al2O3+B2O3+ZrO2) / (R2O+RO)<1.7; Preferably 1<(Al2O3+B2O3+ZrO2) / (R2O+RO)<1.6; Especially preferred is 1.1<(Al2O3+B2O3+ZrO2) / (R2O+RO)<1.5 and / or 0.5 <Al2O3 / (R2O+RO)<1.1; Preferred 0.6 <Al2O3 / (R2O+RO)<0.9; 0.7 is particularly preferred <Al2O3 / (R2O+RO)<0.85 Where R2O=Li2O+K2O+Na2O, and RO=MgO+CaO+SrO+BaO+ZnO.

6. Glass according to any one of the preceding claims, characterized in that The glass contains 0 to 1 mol % SnO 2 , preferably 0.1 to 0.5 mol % SnO 2 and / or 0 to 1 mol % CeO 2 and / or 0 to 1 mol % Cl, wherein the sum of CeO 2 + SnO 2 + Cl is preferably at most 2 mol %.

7. Glass according to any one of the preceding claims, characterized in that The glass is substantially free of coloring components, in particular free of coloring rare earths, in particular Nd2O3, Er2O3, and free of coloring metal oxides, in particular free of V2O5, CoO, NiO, Cr2O3, CuO.

8. The glass according to any one of claims 1 to 6, characterized in that The glass contains coloring components, in particular at least 0.1 mol % and at most 5 mol % of at least one coloring component, the coloring component being particularly preferably selected from CoO, Fe2O3, TiO2, Cr2O3 and / or MnO and / or mixtures thereof.

9. A method for manufacturing the tempered glass according to any one of claims 1 to 8, the method comprising the following steps: - Manufacturing of LABS glass through a melting process, clarification of the glass melt and subsequent hot forming; - at least one ion exchange is carried out in an exchange bath having a composition of 100 wt % to 0 wt % KNO3 and 0 wt % to 100 wt % NaNO3 and 0 wt % to 5 wt % LiNO3, the temperature of the exchange bath being between 370° C. and 500° C. and the duration being between 1 hour and 50 hours.

10. The method according to claim 9, wherein the thermoforming is performed by a drawing process, in particular a float process or a down-draw process, such as overflow fusion or a draw-nozzle process.

11. A cover plate having a thickness of 0.3 mm to 1 mm, made from the tempered glass according to any one of claims 1 to 8 or the method according to claim 9 or 10.

12. Use of the cover plate according to claim 11 and / or a cover plate made of tempered glass according to any one of claims 1 to 8, which is used in electronic devices, in particular in electronic display devices, in particular in mobile electronic display devices, for example, in mobile touch panels and / or mobile digital display devices, such as smartphones or smart watches.

13. A display device, in particular a digital display device, comprising at least one cover plate according to claim 11.

Citation Information

Patent Citations

  • Disc-shaped, chemically tempered or chemically temperable glass article and method for its manufacture

    DE102019121143A1

  • Hot-formed, chemically temperable glass articles with a low crystal content, in particular disc-shaped chemically temperable glass articles, as well as methods and apparatus for their manufacture

    DE102019121146A1

  • Chemically strengthenable lithium aluminosilicate glasses with inherent damage resistance

    US20170197869A1

  • Low viscosity glasses and methods and systems for manufacture

    US20180127302A1

  • Chemically strengthened glass, and glass for chemical strengthening

    US20180186685A1